Examining the efficacy of bystander sexual violence interventions for first- year college students: A systematic review. (September 2019) - Evans, Jennifer L.; Burroughs, Meghan E.; Knowlden, Adam P.
Abstract: Objective: The purpose of the following systematic review was to determine the efficacy of bystander sexual violence, school-based educational interventions, aimed at first-year college students to reduce the occurrence of sexual violence on college campuses. Methods: A literature search was conducted using MEDLINE, CENTRAL, ERIC, and CINAHL Plus and Boolean search logic to extract articles from the databases. Only peer-reviewed journal articles published from 2010 to 2017 were considered. After applying inclusion criteria based on the study purpose, only seven articles remained in the review. Results: Bystander intervention education is effective in increasing student's bystander confidence; however, these results were mixed. Studies in this review employed different educational programs and durations, and instrumentation to assess bystander behavior and confidence. Conclusion: Bystander intervention education is effective in increasing bystander confidence among college students; however, confidence gained during bystander intervention education needs to be assessed. Highlights: Bystander interventions should target first-year college students who are at an increased risk for sexual violence. Bystander practices were utilized, but not all findings were significant. Bystander interventions should continue to be evaluated for efficacy.